A comparison of adherence to hypoglycemic medications between Type 2 diabetes patients with and without serious mental illness - Kreyenbuhl, Julie (2011)
Inadequate self-management of chronic medical conditions like Type 2 diabetes may play a role in the poor health status of individuals with serious mental illnesses. We compared adherence to hypoglycemic medications and blood glucose control between 44 diabetes patients with a serious mental illness and 30 patients without a psychiatric illness. The two groups did not differ in their ability to manage a complex medication regimen as assessed by a performance-based measure of medication management capacity. However, significantly fewer patients with a mental illness self-reported nonadherence to their hypoglycemic regimens compared to those without a mental illness. Although individuals with mental illnesses also had better control of blood glucose, this metabolic parameter was not correlated with adherence to hypoglycemic medications in either patient group. The experience of managing a chronic mental illness may confer advantages to individuals with serious mental illnesses in the self-care of co-occurring medical conditions like Type 2 diabetes.